Assessing the Economic Burden and Benefit-cost of Treating Attention-deficit Hyperactivity Disorder in Germany - Nikolaos Kotsopoulos; Mark P. Connolly; Esther Sobanski; Maarten J. Postma (Journal of Health Economics and Outcomes Research)
# Background Attention-deficit hyperactivity disorder (ADHD) is a condition which has been consistently documented to impact educational outcomes. Children with ADHD are regularly found to have lower educational attainment and increased likelihood of dropping out of school compared to children without ADHD.